Зловживання процесуальними правами учасниками цивільного процесу - Бачинська, Наталія; Сампара, Надія; Bachynska, Nataliia; Sampara, Nadiia (ЗУНУ, 2023)
Досліджено зловживання процесуальними правами учасниками цивільного судочинства, які становлять повноцінне правопорушення, наслідком якого є ускладнення доступу до правосуддя та затягування процесу. Ефективність судового захисту залежить не лише від досконалої процедури розгляду справ, а й від поведінки учасників процесу, добросовісного здійснення ними своїх процесуальних прав і виконання процесуальних обов’язків. Протягом останніх років у цивільному процесі України масового характеру набуло таке негативне явище, як недобросовісне використання сторонами та третіми особами наданих законом процесуальних прав. Встановлення зловживання процесуальним правом на оскарження судового рішення є оціночним та залежить від розсуду суду. Зроблено висновок, що закріплення у цивільному процессуальному законодавстві заборони зловживання процесуальними правами є суттєвим кроком на шляху до підвищення ефективності цивільного процесу. Водночас варто звернути увагу на визначеність та характеристику дій, що можуть бути кваліфіковані як зловживання процесуальними правами, з метою їх відповідності національному та міжнародному законодавству, а також однаковому тлумаченню норм у правозастосовній практиці. The article is devoted to the abuse of procedural rights by participants in civil proceedings, which is a full- fledged offense, resulting in complicated access to justice and delaying the process. The article is devoted to the abuse of procedural rights by participants in civil proceedings, which is a full- fledged offense, resulting in complicated access to justice and delaying the process. The problem of abuse of procedural rights has been and remains quite relevant for the national science and practice, because the correct and timely consideration and resolution of civil cases in conditions of procedural bad faith becomes an extremely difficult task. The Civil Procedure Code of Ukraine in the new edition for the first time among the basic principles of civil proceedings enshrined the provision on the inadmissibility of abuse of procedural rights, defined the actions of persons that can be qualified as abuse, and also provided a mechanism for combating such a negative phenomenon. Abuse of procedural rights is a rather subjective and evaluative concept. At the same time, it should be emphasized that the abuse of the right should be considered as a procedural offense only if a causal link between the abuse and the harm caused (establishment of certain risks) to another party to the case is established. The introduced innovations are quite appropriate, but they are not free from shortcomings, given the inclusion of the most common situations of abuse of civil procedural rights and at the same time ignoring more complex ways of abuse (implicit abuse (for example, abuse of judge’s recusal or filing several different in content/subject claims regarding the same legal relationship), as well as the fact that judges currently do not apply the articles sufficiently. The author concludes that enshrining the prohibition of abuse of procedural rights in the civil procedural legislation is a significant step towards improving the efficiency of civil procedure. At the same time, attention should be paid to the certainty and characterization of actions which may be qualified as abuse of procedural rights, with a view to their compliance with national and international legislation, as well as to the uniform interpretation of the rules in law enforcement practice.
Abuse of procedural rights by participants in civil proceedings
Keywords: зловживання процесуальними правами; зловживання цивільними матеріальними правами; права та обов’язки сторін; принцип неприпустимості зловживання процесуальними правами; відповідальність за зловживання процесуальними правами; abuse of procedural rights; abuse of civil substantive rights; rights and obligations of the parties; principle of inadmissibility of abuse of procedural rights; liability for abuse of procedural rights